INNOVATION STRATEGY OF HEWLETT-PACKARD INDONESIA TO COMPETE IN INFORMATION TECHNOLOGY INDUSTRY - Gunawan, Michael Surya; Huseini, Martani (Jurnal Ilmu Administrasi Negara, 2019)
Innovation Strategy of Hewlett-Packard Indonesia to Compete in Information Technology Industry. Research objectives : 1. Analyze the quality level of Hewlett-Packard (HP) Indonesia services provided to its customers in Indonesia, 2. Analyzing to what extent the delegation of authority of Hewlett-Packard (HP) headquarters to Hewlett-Packard (HP) Indonesia which includes autonomy discretion in innovating both in terms of process and measurement instruments (support). Knowing the information technology industry strategy in the case study is Hewlett-Packard (HP) strategy in building a culture of continuous innovation that can be categorized as a strategic innovation. This study is generated through quantitative and qualitative method by disseminating questinaire to 112 loyal customers which have been at least 3 years experience with Hewlett-Packard (HP) Indonesia as well as have spent at least 1 (one) million US every year and interview top management of Hewlett-Packard (HP) Asia Pacific and Hewlett- Packard (HP) Indonesia. The result of research found human capital and the role of topmanagement have played a very important role-model to implement A-to-F model in innovation and disseminate a socialization, externalization, combination and internalization (SECI) in spiral mode within company to create innovation culture. It is purposed to manage their sustainability of life and growth in a changing strategic environment in Indonesia.